O mercado de trabalho brasileiro para a população migrante - Jesus, Isac Silva de (Brasil, 2024)
This study aimed at analyzing the impact of migration on the Brazilian formal labor market, focusing on the evolution of the proportion of formally employed migrants over the period from 2012 to 2022 and between the different Brazilian States. To achieve this objective, a quantitative methodology was developed integrating descriptive and inferential analysis, using data from the OBMIGRA and RAIS databases. The techniques we used include descriptive statistics and simple linear regression analysis with a log-lin model. The results indicate the profile of the migrant population, in relation to the continent of origin and gender and its spatial distribution among Brazilian states. The analyzes also indicated that the proportion of migrants in formal jobs presents significant variations over time, in the period analyzed. The conclusions point to the need for further studies to understand the attractiveness factors of foreign labor in different Brazilian states, understanding the effect of regional public policies that eventually facilitate the integration of migrants into the labor market and promote greater equity between regions.